Multimedia Mobile Application to Improve the Academic Achievement of Fifth Grade Elementary School Students in Physical Education Classes - Sri Nuraini; Taufik Rihatno; Resha Putri Fadhilla; Arita Marini; Julius Sagita; Desy Safitri; Leola Dewiyani (Journal of Education Reseach and Evaluation, 2024)
Lack of student interest in learning has an impact on low student learning outcomes. One of the factors that causes low student learning outcomes is the lack of learning media. This research aims to examine the effect of multimedia mobile applications to improve the academic achievement of fifth grade elementary school students in physical education classes. This type of research is quantitative research using an experimental design. The population in this study was 112 grade V elementary school students. This research took samples randomly using the Slovin formula. The methods used to collect data are questionnaires and tests. The instruments used to collect data were questionnaire sheets and test questions. The data analysis technique used to analyze the data is inferential statistics. The results of this research, namely the t-test results, show that there is an influence of the use of mobile Apps in learning activities. It can be concluded that the use of mobile Apps in learning activities can improve students' academic achievement in class V physical education. This research implies that the use of mobile Apps in learning activities can make it easier for students to learn.